Evaluating Cybersecurity Investment Strategies in a Medium-Sized Enterprise: A Case Study of a Growing POS Service Provider in Indonesia - Ryan Adhi Nugraha; Muhammad Hafizhuddin Hilman; Setiadi Yazid; Eko Yon Handri (Politeknik Siber Cerdika Internasional, 2026)
Background: As mid-sized businesses use third-party integrations on services like SaaS-based POS systems, cybersecurity expands potential avenues of attack. Many of these organizations engage in reactive cybersecurity, or waiting until something happens instead of preventing it. In the face of increasingly complex organizational architecture, it is imperative to reevaluate whether these reactive approaches are still adequate in guaranteeing operational continuity and data safety. Objective: This research is performed to investigate whether a reactive approach of cybersecurity may still suffice for a medium sized company that expands its operation in Indonesia, which runs over the SaaS POS platform. Method: The study uses a qualitative single-case study design. The data were collected through semi-structure interviews with business and engineering stakeholders, triangulated by supporting organizational documents. Data were analyzed through rubric-based qualitative coding and mapped against a literature-derived reactive–proactive cybersecurity posture rubric in regard to incident response, budget allocation, and layered security infrastructure. Results: The results suggest daily operational readiness is limited by symptom-driven detection systems, periodic and manual monitoring practices, and response schedules dependent on unstructured coordination with follow-ups. There are baseline preventive controls, but many program-level capabilities are nascent—everything from centralized telemetry and alerting, to consistent incident workflow with remediation tracking, balanced against a systematic and periodic cadence of assurance. Conclusion: ..